From the taverns to the rotative hiring systems: Workers, foremen and alcohol at dock work (Chile 1914-1923) - Santibáñez Rebolledo, Camilo Andrés (Universidad Católica del Norte, Instituto de Investigaciones Arqueológicas y Museo, 2021)
This paper is about the hiring practices and mechanisms of favoritism and retribution waged by foremen and workers in some Chilean docks during the first decades of the 20th century. Based on press and business bulletins from the docks of saltpeter and the Concepción area, the conclusion argues that this favoritism was based on a mechanism of retribution constituted mainly by the consumption of alcohol that the workers made in taverns associated with the foremen who nominated the crews. The workers’ way of answering this arbitrariness were the rotating systems for the distribution of the work that they struggled to establish and keep during 1918 and 1923: the “redondilla” and the “turno numerado”.